(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
This paper presents the experimental investigation for producing structural lightweight concrete using three types of lightweight aggregate from different sources of local natural, waste and recycled materials in Iraq and those compared to natural aggregate concrete. In this investigation, the natural porcelanite rocks available in western desert of Iraq used as a coarse aggregate in the first mix. The second mix involving the pumice stone which is obtainable in northern Iraq used as a coarse aggregate. The third mix of structural lightweight concrete produced by using composite aggregates that is formed from 75% recycled of local Iraqi clay bricks and 25% from waste of themestone. All those mixes compared with natural aggregate concrete at the same mix proportions which included minerals and chemical admixtures. In this research, fresh and hardened concrete properties were studied. In hardened concrete state, destructive and non-destructive tests were performed of 28 days. From the work results, it can be concluded that the coarse lightweight aggregate of porcelanite, pumice and composite aggregates can be used instead of natural aggregate (gravel) to make structural lightweight concrete with densities of less than 2000 kg/m3 and this less than the corresponding natural aggregates concrete by the range of (25%-27.4%) with cylinder compressive strength ranged between (25.3-36.1) MPa at 28 days. Many relations were proposed to estimate some of mechanical properties of lightweight aggregate concrete. The ACI318, 2014 expression and some of other codes and literature of researches were used to compare with the proposed experimental relations.